2013
DOI: 10.1002/rnc.3108
|View full text |Cite
|
Sign up to set email alerts
|

Admissibility and static output‐feedback stabilization of singular Markovian jump systems with defective statistics of modes transitions

Abstract: SummaryThis paper presents a necessary and sufficient condition for discrete‐time singular Markovian jump linear systems with defective statistics of modes transitions to be regular, causal, and stochastically stable. The static output‐feedback stabilization problem for discrete‐time singular Markovian jump linear system with defective statistics of modes transitions is studied. Furthermore, the defective statistics about modes transitions are studied by considering the uncertain transition probabilities and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In the proof of the sufficiency of Theorem 3.3 in the work of Liu et al, by using the transformation ζ ( k )= N i x ( k ), the authors claim that the stochastic stability of system (3), ie, Er.5ptfalse(kfalse)1ptx1ptfalse(k+1false)=Ar.5ptfalse(kfalse)1ptx1ptfalse(kfalse), is equivalent to that of system (15). However, the authors have confused E i and E r ( k ) .…”
Section: Commentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the proof of the sufficiency of Theorem 3.3 in the work of Liu et al, by using the transformation ζ ( k )= N i x ( k ), the authors claim that the stochastic stability of system (3), ie, Er.5ptfalse(kfalse)1ptx1ptfalse(k+1false)=Ar.5ptfalse(kfalse)1ptx1ptfalse(kfalse), is equivalent to that of system (15). However, the authors have confused E i and E r ( k ) .…”
Section: Commentsmentioning
confidence: 99%
“…In this section, a new linear matrix inequality (LMI) is proposed. It is shown that it is equivalent to the stochastic admissibility of the type of singular model addressed in the work of Liu et al but with a different assumption (see Assumption in the following).…”
Section: A New Lmimentioning
confidence: 99%
See 1 more Smart Citation
“…When descriptor systems are subjected to stochastic disturbance in their structures, it is reasonable to cast the model into descriptor Markovian jump systems. Recently, a great deal of attention has been devoted to descriptor Markovian jump systems, to name a few, stability and stabilization (e.g., [25][26][27][28][29][30][31]), guaranteed cost control and H ∞ control (e.g., [22]), observer design (e.g., [32]) and monographs [33,34]. Among these published results, Wang and Zhang [28] studied the robust control problem for a class of uncertain singular stochastic Markovian jump systems via proportional-derivative state feedback controllers, but the derivative-term coefficient is assumed to be normalized which can be transformed into the standard state-space Markovian jump systems.…”
Section: Introductionmentioning
confidence: 99%
“…There are also valuable results in positive one-dimensional and two-dimensional (2D) systems. For example, it has shown in [8] that positive one-dimensional and/or 2D systems is one of the latest additions to the communications and control engineering series, and it has reported the major technological advances in this field from academic and industrial institutions around 3510 Y. LIU ET AL.…”
Section: Introductionmentioning
confidence: 99%